Family Firms, Family Boundary Organizations, and the Family-Related Organizational Ecosystem. (December 2021) - De Massis, Alfredo; Kotlar, Josip; Manelli, Luca
While entrepreneurial families often expand their activity over multiple businesses and patrimonial assets, this complexity is rarely addressed in mainstream family business research, where the predominant focus is on the family business or, at best, on the family controlling the operational business. We advance a more holistic understanding of entrepreneurial families that contemplates the variety of assets they create or acquire over time that jointly generate financial and socioemotional wealth for the family, and call for attention to the variety of organizations that entrepreneurial families establish to preserve, manage, and/or administer such assets. We theorize that each of these organizations can be devised as a family boundary organization (FBO), which operates at the interface of the entrepreneurial family and other systems, and such FBOs form a family-related organizational ecosystem . We propose a new framework that extends the scope of research beyond the family business and focuses more directly on entrepreneurial families and on the boundaries between the entrepreneurial family, its multiple assets, and the FBOs in the family-related organizational ecosystem . This framework paves the ground to extend the three-circle model, broadening the scope of family business research to consider a wider range of organizations besides the family firm, such as family foundations, family business foundations, family offices, family holdings, family academies, and family museums. Drawing on the organizational boundaries literature, we integrate organizational boundaries in the theory of the family firm and propose a research agenda to examine the entrepreneurial family and its assets in a broader way.